EFFECT OF NON-POLLUTING AND RENEWABLE LOAD ON DELAMINATION OF A COMPOSITE BIOMECHANICAL MATERIAL - Benzerga, D.; Haddi, A.; Lavie, A. (Journal of Mechanical Engineering and Technology (JMET), 2014)
The objective of this paper is to develop a delamination model that can predict delamination growth in a new woven composite for orthopedic use. This composite material is obtained from a laminated composite woven by incorporating a natural organic load (granulates of date cores) which becomes hybrid composite. The composite is made of an organic matrix containing methyl methacrylate, a woven reinforcement including a reinforcing glass fiber and a fabric perlon having an absorbing role. The walk cycle has been used to determine the operating conditions of tibiae prosthesis. Hence, the deflection tests were validated by orthopedist experts. Three end-notched flexure (3ENF) tests were carried out on the new woven composite to detect delamination phenomenon. The formulation is based on damage mechanics and uses only two constants for delamination damage. We assume that the interface has a bi-linear softening behaviour and regarded as being a whole of several interfacial bonds. The model has been implemented into the commercial (FE) code. Numerical simulations were carried out in end-notched flexure (3ENF) tests to detect initiation and growth of delamination in the new woven composite.